Charles Bowdoin Fillebrown papers - Fillebrown, Charles Bowdoin, 1842-1917.
Correspondence, speeches, printed matter, and other papers relating to Fillebrown's promotion of the single tax and the activities of the Massachusetts Single Tax League. Correspondents include Thomas Nixon Carver, John Bates Clark, John R. Commons, Richard T. Ely, Frank A. Fetter, Max Hirsch, Alvin Saunders Johnson, J. Shield Nicholson, Carl C. Plehn, Edwin R.A. Seligman, F.W. Taussig, Carroll Davidson Wright, and Allyn Abbott Young.
Economist and author.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Carver, Thomas Nixon, -- 1865-1961 -- Correspondence; Clark, John Bates, -- 1847-1938 -- Correspondence; Commons, John R. -- 1862-1945 -- Correspondence; Ely, Richard T. -- 1854-1943 -- Correspondence; Fetter, Frank A. -- 1863-1949 -- Correspondence; Hirsch, Max, -- 1853-1909 -- Correspondence; Johnson, Alvin Saunders, -- 1874-1971 -- Correspondence; Nicholson, J. Shield -- 1850-1927 -- Correspondence; Plehn, Carl C. -- 1867- -- Correspondence; Seligman, Edwin R. A. -- 1861-1939 -- Correspondence; Taussig, F. W. -- 1859-1940 -- Correspondence; Wright, Carroll Davidson, -- 1840-1909 -- Correspondence; Young, Allyn Abbott, -- 1876-1929 -- Correspondence; Massachusetts Single Tax League; Single tax; Authors; Economists